PENGARUH LATIHAN PASSING SEGI TIGA TERHADAP KEMAMPUAN PASSING BAWAH PERMAINAN BOLA VOLI ATLET JUNIOR DISHUB KOTA PEKANBARU - Hartono, Rudi; Sulastio, Agus; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to determine the effect of triangle passing drills onthe ability of underhand passing in volleyball games among junior athletes of DISHUBKota Pekanbaru. The research uses an experimental method with a one-group pretest-posttest design approach. The study population consisted of 30 junior volleyball playersfrom DISHUB Kota Pekanbaru. The instrument used was an underhand passing test tomeasure passing skills. The data obtained were analyzed using descriptive statistics,normality tests, and t-tests. The results showed that the t-value of the experimentalgroup was greater than the t-table value, which was 4.631 compared to 2.131, thus thehypothesis was accepted. Similarly, the t-value of the control group was greater thanthe t-table value, which was 3.368 compared to 2.131, thus the hypothesis wasaccepted. Data shows that triangle passing drills increase the underhand passingability of junior athletes of DISHUB Kota Pekanbaru by 28.40%. This is 17.34% higherthan the control group, which did not use triangle passing drills and only achieved11.06%.Keywords: Triangle Passing Drills, Underhand Passing, Volleyball